1990
DOI: 10.1104/pp.94.4.1682
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Five Abscisic Acid-Responsive cDNA Clones Isolated from the Desiccation-Tolerant Plant Craterostigma plantagineum and Their Relationship to Other Water-Stress Genes

Abstract: [1988] Plant Mol Biol II: 277-291). Secondary structure predictions are discussed and suggest that the deduced proteins could play a role in protecting core cell structures in a dehydrated cell. It is concluded that at least in part the gene products involved in the desiccation-induced pathways are common to leaves of resurrection plants and embryos. Two cDNA clones appear to code for Craterostigma-specific mRNAs. The expression patterns of all five transcripts were studied in comparison to desiccated leaves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
180
1
2

Year Published

1991
1991
2009
2009

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 244 publications
(186 citation statements)
references
References 21 publications
3
180
1
2
Order By: Relevance
“…The late embryogenesis abundant (LEA) proteins were first found in plant seeds (Dure et al, 1981) and subsequently also in vegetative tissues under different stresses, such as salinity, cold, and drought (Hundertmark and Hincha, 2008). Previous studies have shown that LEA-encoding genes are strongly enhanced in the desiccation-tolerant plants during drying (Piatkowski et al, 1990;Hundertmark and Hincha, 2008); therefore, they might be important for the acquisition of desiccation tolerance (Bartels and Sunkar, 2005). Dehydrins (also classified as group 2 LEA) have been shown to act as key components of dehydration tolerance (Close, 1996(Close, , 1997Zhu et al, 2000;Allagulova Ch et al, 2003).…”
Section: Metabolism Adjustment In Response To Desiccationmentioning
confidence: 99%
“…The late embryogenesis abundant (LEA) proteins were first found in plant seeds (Dure et al, 1981) and subsequently also in vegetative tissues under different stresses, such as salinity, cold, and drought (Hundertmark and Hincha, 2008). Previous studies have shown that LEA-encoding genes are strongly enhanced in the desiccation-tolerant plants during drying (Piatkowski et al, 1990;Hundertmark and Hincha, 2008); therefore, they might be important for the acquisition of desiccation tolerance (Bartels and Sunkar, 2005). Dehydrins (also classified as group 2 LEA) have been shown to act as key components of dehydration tolerance (Close, 1996(Close, , 1997Zhu et al, 2000;Allagulova Ch et al, 2003).…”
Section: Metabolism Adjustment In Response To Desiccationmentioning
confidence: 99%
“…Among the latter, Craterostigma plantagineum (Scrophulariaceae) has been used as model system for molecular analyses of desiccation tolerance. Most studies of Craterostigma have focused on the characterization of genes induced by dehydration [21,22]. Many of these genes show sequence homologies with genes abundantly expressed in desiccation-tolerant zygotic embryos [reviewed in 3,4].…”
mentioning
confidence: 99%
“…The former clone is closely related to the dhn3 clone isolated from desiccated barley seedings by Chandler et al (1988) and to clone rab 16 isolated by Mundy and Chua (1988) from ABA-treated rice. Both pESI18 and pESI35 are also related to clones pcC6-19 and pcC27-04 isolated from a water-stressed resurrection plant (Piatkowski et al 1990). The remaining nine partial cDNA clones showed no homology to each other or any other reported DNA sequence (Gulick and Dvo~fik 1992).…”
Section: Introductionmentioning
confidence: 99%